UNVEILING THE SIGNIFICANCE OF ANGEL ISLAND IMMIGRATION STATION AND SAN FRANCISCO CHINATOWN IN CHINESE AMERICAN LITERATURE (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This paper explores the historical and literary significance of Angel Island Immigration Station and San Francisco Chinatown in Chinese American diaspora literature. These two locations are pivotal in understanding the experiences of the first and second generations of Chinese immigrants in the United States. Angel Island, designed to detain non-European immigrants, subjected Chinese detainees to harsh conditions and rigorous examinations, with many expressing their anguish through poetry carved into the walls. These poems, collected in Island: Poetry and History of Chinese Immigrants on Angel Island 1910-1940, serve as a powerful testament to their struggles and resilience. San Francisco Chinatown, established during the Gold Rush, became a cultural and social hub for Chinese immigrants, retaining its customs and identity amidst adversity. This enclave is frequently depicted in Chinese American literature, reflecting the community's perseverance and cultural richness. Through the lens of these locations, this paper highlights the significant role they play in documenting and reflecting the Chinese American immigrant experience, offering insights into the broader themes of immigration, identity, and resilience.